Antidiabetic effect of oral supplementation with Caulerpa racemosa powder - Nassima El Habitri; Louiza Belkacemi (European Journal of Biological Research, 2022)
Algae are known for their high nutritional value and the presence of bioactive compounds with anti-diabetic activity. In this study, the effects of oral supplementation with the whole powdered green alga Caulerpa racemosa was assessed on biochemical and organic parameters in rat model of type 2 diabetes.  Type 2 diabetes model (DM) was induced by high fat diet (HFD) (5.75 kcal/g) combined to streptozotocin injection (35 mg/kg). The DM-C500 and DM-C1000 groups were maintained on HFD and supplemented orally during four weeks with powdered C. racemosa at 500 and 1000 mg/kg of body weight, respectively. The DM-C0 group was fed with HFD without C. racemosa supplementation. All the experimental rats were maintained on HFD during the 30 days of experiment. C. racemosa at 500 mg/kg improved fasting glycaemia and glucose tolerance. The IPGTT test revealed a decrease (p<0.05) in the fasting glycaemia recorded at the 120th min from day 0 (534 ± 38.88 mg/dL) to day 30 (326 ± 63.05 mg/dL). C. racemosa supplementation prevented liver lipid peroxidation in DM-C500 and DM-C1000 group (12.94 ± 2.20 and 10.48 ± 1.15 nmol MDA/g, respectively) compared to DM-C0 group (35.49 ± 2.30 nmol MDA/g). Caulerpa racemosa at 500 mg/kg, and relatively at 1000 mg/kg, alleviated pancreatic, liver and renal tissue damages compared to DM-C0 groups which displayed injuries in their histological sections. Caulerpa racemosa oral supplementation could represent a possible natural approach to prevent organic and metabolic disorders related to type 2 diabetes.